The Time of the Creation of Kanun: An Hystorical Observation through the Terminology - Aliu, Alket (Richtmann Publishing, 2021)
Different scholars are of different opinions regarding the time when the entity of the Albanian traditional law known as â€œKanuni i Leke Dukagjinitâ€ was compiled, precisely the law which reigned supreme in the highlands of Northern Albania. They offer their arguments based on historical data, mainly but also tapping other sources. In order to resolve such a mystery, we can obtain important data through the analyses of the language and terminology used by Father Shtjefen Gjecovi, when he gathered and compiled the Albanian oral tradition of Kanun. The time when Kanun began to govern the life of the inhabitants of Northern Albania is quite important as in this way we can gauge the evolution of the terminology used in the Kanun up to the point that the oral tradition was gathered, compiled and written down by Father Shtjefen Gjecovi at the beginning of the last century. Such a terminology helps us to come to the conclusion that in spite of the fact that Kanun existed many centuries ago, there are a lot of different strata in it up to the modern times ones. Received: 7 March 2021 / Accepted: 26 April 2021 / Published: 17 May 2021